Influence of Nollywood Movies Representation of the Elderly on Attitudes to the Aged in Western Nigeria - Omotola Ogunbola (Lakhomi Journal Scientific Journal of Culture, 2024)
The portrayal of elderly characters in Nollywood movies can significantly shape public attitudes toward the aged in Western Nigeria, given the prominent role of Nollywood in Nigerian culture. Nollywood has a powerful influence on shaping societal views on aging in Western Nigeria. Portrayals that emphasize respect, wisdom, and positive aging can help foster supportive and respectful attitudes toward the elderly, while negative stereotypes can perpetuate ageism. The objectives of the paper are to examine the representation of the elderly in films and the common themes in Nollywood movies. This paper adopted the Representation Theory. The theory explains how stereotypical representations of the elderly in films are done. Certain ideologies or viewpoints which may be considered ageist against the elderly are sometimes portrayed in movies. Since media contributes to the creation and reinforcement of stereotypes, an application of this theory informs the intention to use in-depth interview to interact with film makers of the need to make movies which are anti-stereotypical representations of ageing process and the aged. The paper is a conceptual paper, which utilises secondary data based on the existing literature like journal articles, textbooks and online materials. The paper argues that in the traditional African societies the elderly are also revered. Aged members of a community are seen as culture-bearers, philosophers, professors and visionaries. The traditional Nigerian society is not left in this regard. The African world view regards old age as, reward to those who are just, chaste, kind, charitable, and upright in their doing with others. No wonder, the old people were usually regarded as living ancestors.